2012
DOI: 10.1111/j.1365-2516.2012.02934.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the outcome of prophylaxis, on‐demand treatment or combined treatment in 18–35‐year old men with severe haemophilia in six countries

Abstract: Summary.A number of studies have been published on the benefits of prophylactic treatment in adults with haemophilia. However, in many countries, it is considered as optional due to financial constraints. This survey was carried out to examine the long-term effects of prophylaxis and the continuing benefit of the treatment into adulthood. Self-assessed health-related data and the EQ-5D questionnaire measuring health utility were collected from 124 men (26.9 ± 4.6 years) from Canada (N = 40), France (N = 14), I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 17 publications
4
77
3
2
Order By: Relevance
“…By facilitating timely treatment of a bleed, SI helps to preserve independence [18]. The increasing use of adult prophylactic regimens in developed countries adds to the need for SI skills [19]. We noted that SI use did not peak until 29–30 years among all severities, indicating that older teens and young adults may benefit from additional training.…”
Section: Discussionmentioning
confidence: 98%
“…By facilitating timely treatment of a bleed, SI helps to preserve independence [18]. The increasing use of adult prophylactic regimens in developed countries adds to the need for SI skills [19]. We noted that SI use did not peak until 29–30 years among all severities, indicating that older teens and young adults may benefit from additional training.…”
Section: Discussionmentioning
confidence: 98%
“…Only the study by Steen Carlsson et al [34]. From a patient perspective, most data suggest that prophylaxis is associated with a considerable increase in quality of life [38]. All studies reported that prophylaxis was associated with a significant reduction of bleeding.…”
Section: Prophylaxis Versus On-demand Therapy: Issues Of Cost-effectimentioning
confidence: 99%
“…Observational studies support that prophylactic treatment reduces mobility problems, pain and discomfort, and the need for assistance; it is also associated with higher productivity and a better QOL [11-13]. PWH receiving prophylactic treatment from early childhood have better outcomes than those who are initially treated on demand and only subsequently switch to prophylactic treatment [6, 12, 14-16]. …”
Section: Introductionmentioning
confidence: 99%
“…While a consensus exists regarding the benefits of prophylactic treatment in childhood, the optimal treatment strategy and dosage is still under debate, in particular for adult PWH [6, 12, 17]. There are different national strategies: high-dose prophylaxis (e.g., in Sweden), intermediate-dose prophylaxis (e.g., in The Netherlands), and on-demand treatment (e.g., in Russia) [13, 18].…”
Section: Introductionmentioning
confidence: 99%